Morphological and conductivity studies of di-ureasil xerogels containing lithium triflate - Correia, Silvia Gomes (2002)
Sol–gel derived poly(oxyethylene)/siloxane hybrids doped with lithium triflate, LiCF3SO3, have been investigated. The host hybrid matrix of these materials, named di-ureasil and represented by U(600), is composed by a siliceous framework to which polyether chains containing 8.5 oxyethylene repeat units are covalently bonded through urea linkages. Xerogel samples U(600)nLiCF3SO3 with n (where n is the molar ratio of oxyethylene moieties per Li+ ion) between ∞ and 0.1 have been examined. X-ray diffraction and differential scanning calorimetry have provided conclusive evidence that the xerogels analyzed are entirely amorphous. The salt-rich material with n=1 exhibits the highest conductivity over the whole range of temperature analyzed (e.g. 4.3×10−6 and 2.0×10−4 Ω−1 cm−1, respectively, at 25 and 94 °C).